The Effect of Work Motivation and Discipline on Employee Performance: In one of the District Offices of Bandung Regency - Nabilah Nurislam; Maulana Yusup; Sana Sholihah; Lungguh Jatmika (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aims to determine whether there is a significant influence between work motivation and work discipline on employee performance. The object of research is 50 employees in one of the sub-district offices of Bandung Regency using a questionnaire so that data is taken using the population. The variables in this study are divided into two, namely, independent and dependent variables. The independent variable divides into motivation and work discipline, and the dependent variable is employee performance. This study uses using the SPSS version 16 application. Research using Path Analysis shows that the variable Motivation (X1) has a direct effect of 26.0%, an indirect effect through a relationship with Work Discipline (X2) of 15.9%, and the total effect is 41.9%. The Work Discipline Variable (X2) has a direct effect of 20.7% and an indirect effect through its relationship with motivation (X1) of 15.9%. The total effect is 36.6%. The results of the relationship of the coefficient of determination (R square) with the variable Work Motivation (X1) and Work Discipline (X2) in determining the Employee Performance variable (Y) is 78.5%. In comparison, other factors that affect employee performance but are not examined show by the value of € = 0.215 or 21.5%. As for suggestions concerning the research results, agencies should be able to improve the above variables further.